2013
DOI: 10.1121/1.4803846
|View full text |Cite
|
Sign up to set email alerts
|

The role of diffusive architectural surfaces on auditory spatial discrimination in performance venues

Abstract: In musical or theatrical performance, some venues allow listeners to individually localize and segregate individual performers, while others produce a well blended ensemble sound. The room acoustic conditions that make this possible, and the psycho-acoustic effects at work are not fully understood. This research utilizes auralizations from measured and simulated performance venues to investigate spatial discrimination of multiple acoustic sources in rooms. Signals were generated from measurements taken in a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The values of this parameter at the positions close to the lateral wall were different for the DM and DF conditions. Robinson et al [64] showed that the correlation between the impulse responses at two ears at positions close to any surface is lower due to effects of the surface proximity on the impulse response of the ear oriented towards it. In this way, the binaural impulse response is affected asymmetrically on each ear channel (left and right).…”
Section: Discussionmentioning
confidence: 99%
“…The values of this parameter at the positions close to the lateral wall were different for the DM and DF conditions. Robinson et al [64] showed that the correlation between the impulse responses at two ears at positions close to any surface is lower due to effects of the surface proximity on the impulse response of the ear oriented towards it. In this way, the binaural impulse response is affected asymmetrically on each ear channel (left and right).…”
Section: Discussionmentioning
confidence: 99%
“…We could extend this result stating that in Italian-style opera houses, there are very often problems of focalization of the sound field especially in the stalls and in the boxes (mainly in the first order) Moreover, several authors found that diffusion and scattering in Opera Houses represent a fundamental issue, [18][19][20] to be measured [21][22][23] or simulated. 24,25 This phenomenon leads to design special devices, as diffusing panels, that could be inserted in the theatres, to avoid focalization and improve the acoustic quality.…”
Section: The Acoustic Design Of Sound Diffusion In Three Italian Opermentioning
confidence: 99%
“…It reduces the phase coherence of sound signals that might reduce the clarity and the quality of bass [31]. Moreover, a reflection from a scattering surface makes the localization worse than a reflection from a flat or absorptive wall [32]. Scattering elements, in many modern cases, are on a similar scale throughout the hall, resulting in the attenuation of only certain frequencies.…”
Section: Side Walls Without Small Widespread Diffusing Elementsmentioning
confidence: 99%